2017
DOI: 10.1002/jmor.20671
|View full text |Cite
|
Sign up to set email alerts
|

Morphological specializations of the yolk sac for yolk processing in embryonic corn snakes (Pantherophis guttatus: Colubridae)

Abstract: Non-avian reptiles commonly are assumed to be like birds in their overall patterns of development. However, colubrid corn snakes (Pantherophis guttatus) have mechanisms of yolk cellularization and processing that are entirely different from the avian pattern. In birds, a vascular "yolk sac" surrounds and digests the liquid yolk. In contrast, in corn snakes, the yolk material is converted into vascularized cords of yolk-filled cells. In this study, we used stereomicroscopy, histology, and scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 35 publications
6
37
0
Order By: Relevance
“…First, the granular cells are much smaller than the endodermal cells; second the granular cells never contain yolk droplets; and third, no structural intermediates exist between the two populations. The cells appear to be equivalent to granulocyte‐like cells described in other squamates, including both lizards (Stewart and Florian, ; Stewart et al., ; Stewart and Thompson, ) and snakes (Blackburn et al., ; Powers and Blackburn, ; Stewart and Thompson, ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…First, the granular cells are much smaller than the endodermal cells; second the granular cells never contain yolk droplets; and third, no structural intermediates exist between the two populations. The cells appear to be equivalent to granulocyte‐like cells described in other squamates, including both lizards (Stewart and Florian, ; Stewart et al., ; Stewart and Thompson, ) and snakes (Blackburn et al., ; Powers and Blackburn, ; Stewart and Thompson, ).…”
Section: Discussionsupporting
confidence: 56%
“…Our observations on the pattern of yolk processing in L. getula and L. triangulum reveal interesting similarities to some other squamates that have been appropriately studied. Not only is this pattern similar to that of the corn snake Pantherophis guttatus (Powers and Blackburn, ), but it appears to resemble that of certain lizards. Sparse information from light microscopy suggests that yolk‐filled endodermal cells surround small blood vessels in the eggs of two oviparous lizards (Romano et al., ; Stewart et al., ) and a viviparous one (Weekes, ) (see Elinson et al., ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This investigation is part of a research program focused on yolk processing patterns in developing reptile embryos, as called for in a recent review (Elinson et al, ). A subsequent series of papers demonstrated that lizard and snake embryos process yolk for development by an overall pattern that differs from that of birds (Blackburn et al, ; Powers & Blackburn, ; Stewart & Thompson, ). The present study on T. scripta reveals that chelonians have a pattern of yolk processing that is similar or identical to that of squamate reptiles, thereby corroborating preliminary observations on the snapping turtle C. serpentina (Blackburn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has challenged these assumptions by revealing that some reptiles process yolk for embryonic development very differently than do birds (Elinson & Stewart, ; Elinson, Stewart, Bonneau, & Blackburn, ). Notably, in representative snakes and lizards, the yolk sac cavity becomes filled with a compact meshwork of elongated “spaghetti‐like” strands, each of which consists of yolk‐filled endodermal cells arranged in a monolayer around an anastomosing blood vessel (Blackburn, Lestz, Barnes, Powers, & Langkilde, ; Powers & Blackburn, ; Stewart & Thompson, ). By means of these unusual structures, yolk nutrients are cellularized, digested, and made available for transport back to the embryo.…”
Section: Introductionmentioning
confidence: 99%